2006
DOI: 10.1111/j.1398-9995.2006.01268.x
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the determination of serum‐specific IgE antibodies in the diagnosis of immediate β‐lactam allergy

Abstract: These results indicate that, although the specificity of beta-lactam-specific IgE measurement is good, sensitivity is low. Immunoglobulin E measurement should be limited to patients with a clinical history of anaphylactic shock and negative skin tests in order to avoid a drug provocation test. More sensitive assays should be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
2
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(141 citation statements)
references
References 12 publications
5
124
2
10
Order By: Relevance
“…The sensitivity of ImmunoCAP was found to be higher in cases where the patient's allergic reaction was anaphylaxis, while the sensitivity of a non-commercial RAST assay was highest in patients who had anaphylactic shock with hypotension [165]. Positive and negative predictive values were estimated at 45% and 77.1% with ImmunoCap and 18.5% and 81.5% with RAST.…”
Section: Laboratory Investigationsmentioning
confidence: 95%
“…The sensitivity of ImmunoCAP was found to be higher in cases where the patient's allergic reaction was anaphylaxis, while the sensitivity of a non-commercial RAST assay was highest in patients who had anaphylactic shock with hypotension [165]. Positive and negative predictive values were estimated at 45% and 77.1% with ImmunoCap and 18.5% and 81.5% with RAST.…”
Section: Laboratory Investigationsmentioning
confidence: 95%
“…Specific IgE can be measured for limited number of drugs including penicillins, insulin, muscle relaxants and quinolones. Although its sensitivity is low, recent studies have reported that it is positive in patients with a history of anaphylaxis (31). Since not only the drug itself but also its metabolites can be allergen, the value of measuring specific IgE is low.…”
Section: In Vitro Diagnostic Testsmentioning
confidence: 99%
“…Since not only the drug itself but also its metabolites can be allergen, the value of measuring specific IgE is low. Sensitivity for penicilloylIgE which is measured for the major determinant of penicilin (PPL) was reported to be 65-85% compared to skin test and 32-50% compared to the combination of skin test and drug stimulation test (31,32). Minor determinant penicilin IgE antibodies are not measured.…”
Section: In Vitro Diagnostic Testsmentioning
confidence: 99%
“…Hence, false negative results may occur, as is well recognised with penicillin. 8 False positive specific IgE results are also recognised. 9 Therefore, NICE recommends that specific IgE testing is not used to diagnose drug allergy in a non-specialist setting.…”
Section: What Can We Do In the Drug Allergy Clinic?mentioning
confidence: 99%